COMPARATIVE STUDY OF 0.5% BUPIVACAINE AND 0.5% BUPIVACAINE WITH DEXMEDETOMIDINE FOR SPINAL ANAESTHESIA - KANASE, NASEEMA V.; NAVEEN, NAVEEN KUMAR; GAUTAM, ARCHNA; PINGALE, S. A.; BHOSALE, AVINASH J.; GANDHI, SAUDAMINI (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2021)
Spinal anaesthesia remains one of the basic methods in the arsenal of modern aesthetics, which has diminished its prevalence over the last 100 years since its introduction into clinical practise. Stop physiological and metabolic changes that alleviate the discomfort of general anaesthesia during surgery. As the optimum condition for surgery is given. The purpose of this study was to evaluate the effects of dexmedetomidine added to hyperbaric bupivacaine for spinal anesthesia. The design of our study consisted of 75 patients, aged 18 to 50, undergoing ASA physical condition I, II spinal anesthesia undergoing elective lower limb orthopedic surgery, who were randomly assigned three after taking informed consent was divided into groups. The addition of dexmedetomidine to 0.5 per cent of hyperbaric bupivacaine in spinal anaesthesia greatly decreases onset time, prolonging the duration of both sensory and motor blockade.